Equity valuation of Marriott International - Simões, Ana Vanessa Cardoso (2021)
Marriott International is a reference in the hotel industry. The company was founded in 1927 by the Marriott family and over the years has gained the trust and loyalty of its customers. Marriott is also recognized for its excellent management skills, having these been highlighted during the 2008 crisis where the company showed a good performance. This management skills are now being tested by the coronavirus pandemic that is having a severe impact on the company's financials. The goal of this master's project is to determine the fair value of Marriott's shares in order to provide an investment recommendation to possible investors. The ultimate result will be a statement of whether investors should buy, hold or sell the company's shares based on the potential appreciation or depreciation in relation to the market. After a revision of what has been developed in the finance field about company's valuation, two different methodologies will be applied to Marriott International. The Free Cash Flow to the Firm will be the first model to be applied followed by a Relative Valuation that will help us to reach more accurate results. Marriott is a listed company on Nasdaq and on the 31st of December of 2019 the company's stock was worth $150.83, being that we further considered this price as overvalued in the course of the discuss of the valuation results. Our final recommendation stands that investors should sell the shares of Marriott International.